The Implementation of Autonomous Learning through Multimedia Oral Presentation to Develop Students’ Language Skills - Supriadi, Supriadi; Rozelin, Diana; Muhaimin, Muhaimin; Fauzan, Umar (Register Journal, 2024)
Autonomous learning has been implemented in various disciplines. In English Language Teaching (ELT), implementing autonomous learning through multimedia oral presentation could be one of the major strategies to develop students’ language skills. This study aims to investigate the implementation of autonomous learning through a multimedia oral presentation as well as its challenges and obstacles fostering the significant development of language skills among students at an Islamic university. The study involved thirteen students majoring English Education regarded as students of the Z generation. The primary data was obtained through a video project-based multimedia oral presentation, a semi-structured interview with open-ended questions. The observation of the videos with note taking and comments on YouTube were used as secondary data. Through a descriptive qualitative approach, a content analysis technique was used to investigate to what extent the implementation of autonomous learning through a multimedia oral presentation develops students’ language skills. The study found that the students’ performances ranged from competent to somewhat competent in their vocabulary and content coverage; and competent to minimally competent in their grammatical accuracy, pronunciation, comprehensibility, and presentation skills. Implementing the students’ autonomous learning did not significantly develop their language skills due to students' lack of language proficiency, the absence of feedback,  technical challenges, time constraints, and motivation. This suggests that the implementation of students’ autonomous learning     with guidance is necessary to raise students’ language proficiency and minimize the obstacles and challenges, and various technological tools with technical and practical strategies should be familiarized with the students.